Accurate measurement of ground shock with cellular solid. (November 2020) - Wang, Xiaojuan; Li, Yongsheng; Zhou, Hongyuan; Dai, Huliang; Jayasinghe, Laddu Bhagya
Highlights: Match of acoustic impedance is proposed to improve the ground vibration measurement accuracy. A sensor is installed into a cellular solid casing, whose acoustic impedance is designable. The proposed approach is investigated with a field test and theoretical analysis. Abstract: Ground vibration induced by subsurface detonations in geological media such as soil, termed as ground shock, has long been measured for decades, since the free field time history and peak intensity of the shock is the incident load to underground structures and important for design. To address the affected measurement accuracy due to acoustic impedance mismatch, a simple but effective approach is proposed: A sensor is embedded into a cellular solid casing before being installed in soil, whose acoustic impedance is designed to be the same as that of the surrounding soil to eliminate the reflection between the soil-casing interface while the relative motion between the sensor and casing is minimized. A field test and theoretical analysis are conducted to investigate the proposed approach, and it is found that the accuracy of ground shock measurement is improved.